Crypto news and policy innovations: Are European markets affected? - Luca Barbaglia; Mario Bellia; Erica Francesca Di Girolamo; Caterina Rho (European Commission, 2024)
Digital and crypto currencies are becoming an integral part of financial markets. Nevertheless, regulation of these markets seems still at an early stage and the literature evaluating the impact of policy interventions is scarce. We investigate the reaction of crypto markets in the aftermath of a policy announcement using textual information from news and sentiment analysis. Our findings are threefold. First, there is evidence of peaks in news about crypto-assets in correspondence of the date of new developments in EU legislation, in particular about Central Bank Digital Currencies. Second, we find that both returns of cryptocurrencies and general stock market returns are directly proportional to the news sentiment about crypto markets. Third, our event study shows that the introduction of regulation on digital and crypto currencies is perceived as a negative shock by financial markets, especially for digital currencies.
Keywords: C55; E42 G41; 330; cryptocurrencies; digital finance; text mining